Theory HOL-Combinatorics.Orbits
section ‹Permutation orbits›
theory Orbits
imports
"HOL-Library.FuncSet"
"HOL-Combinatorics.Permutations"
begin
subsection ‹Orbits and cyclic permutations›
inductive_set orbit :: "('a ⇒ 'a) ⇒ 'a ⇒ 'a set" for f x where
base: "f x ∈ orbit f x" |
step: "y ∈ orbit f x ⟹ f y ∈ orbit f x"
definition cyclic_on :: "('a ⇒ 'a) ⇒ 'a set ⇒ bool" where
"cyclic_on f S ⟷ (∃s∈S. S = orbit f s)"
lemma orbit_altdef: "orbit f x = {(f ^^ n) x | n. 0 < n}" (is "?L = ?R")
proof (intro set_eqI iffI)
fix y assume "y ∈ ?L" then show "y ∈ ?R"
by (induct rule: orbit.induct) (auto simp: exI[where x=1] exI[where x="Suc n" for n])
next
fix y assume "y ∈ ?R"
then obtain n where "y = (f ^^ n) x" "0 < n" by blast
then show "y ∈ ?L"
proof (induction n arbitrary: y)
case (Suc n) then show ?case by (cases "n = 0") (auto intro: orbit.intros)
qed simp
qed
lemma orbit_trans:
assumes "s ∈ orbit f t" "t ∈ orbit f u" shows "s ∈ orbit f u"
using assms by induct (auto intro: orbit.intros)
lemma orbit_subset:
assumes "s ∈ orbit f (f t)" shows "s ∈ orbit f t"
using assms by (induct) (auto intro: orbit.intros)
lemma orbit_sim_step:
assumes "s ∈ orbit f t" shows "f s ∈ orbit f (f t)"
using assms by induct (auto intro: orbit.intros)
lemma orbit_step:
assumes "y ∈ orbit f x" "f x ≠ y" shows "y ∈ orbit f (f x)"
using assms
proof induction
case (step y) then show ?case by (cases "x = y") (auto intro: orbit.intros)
qed simp
lemma self_in_orbit_trans:
assumes "s ∈ orbit f s" "t ∈ orbit f s" shows "t ∈ orbit f t"
using assms(2,1) by induct (auto intro: orbit_sim_step)
lemma orbit_swap:
assumes "s ∈ orbit f s" "t ∈ orbit f s" shows "s ∈ orbit f t"
using assms(2,1)
proof induction
case base then show ?case by (cases "f s = s") (auto intro: orbit_step)
next
case (step x) then show ?case by (cases "f x = s") (auto intro: orbit_step)
qed
lemma permutation_self_in_orbit:
assumes "permutation f" shows "s ∈ orbit f s"
unfolding orbit_altdef using permutation_self[OF assms, of s] by simp metis
lemma orbit_altdef_self_in:
assumes "s ∈ orbit f s" shows "orbit f s = {(f ^^ n) s | n. True}"
proof (intro set_eqI iffI)
fix x assume "x ∈ {(f ^^ n) s | n. True}"
then obtain n where "x = (f ^^ n) s" by auto
then show "x ∈ orbit f s" using assms by (cases "n = 0") (auto simp: orbit_altdef)
qed (auto simp: orbit_altdef)
lemma orbit_altdef_permutation:
assumes "permutation f" shows "orbit f s = {(f ^^ n) s | n. True}"
using assms by (intro orbit_altdef_self_in permutation_self_in_orbit)
lemma orbit_altdef_bounded:
assumes "(f ^^ n) s = s" "0 < n" shows "orbit f s = {(f ^^ m) s| m. m < n}"
proof -
from assms have "s ∈ orbit f s"
by (auto simp add: orbit_altdef) metis
then have "orbit f s = {(f ^^ m) s|m. True}" by (rule orbit_altdef_self_in)
also have "… = {(f ^^ m) s| m. m < n}"
using assms
by (auto simp: funpow_mod_eq intro: exI[where x="m mod n" for m])
finally show ?thesis .
qed
lemma funpow_in_orbit:
assumes "s ∈ orbit f t" shows "(f ^^ n) s ∈ orbit f t"
using assms by (induct n) (auto intro: orbit.intros)
lemma finite_orbit:
assumes "s ∈ orbit f s" shows "finite (orbit f s)"
proof -
from assms obtain n where n: "0 < n" "(f ^^ n) s = s"
by (auto simp: orbit_altdef)
then show ?thesis by (auto simp: orbit_altdef_bounded)
qed
lemma self_in_orbit_step:
assumes "s ∈ orbit f s" shows "orbit f (f s) = orbit f s"
proof (intro set_eqI iffI)
fix t assume "t ∈ orbit f s" then show "t ∈ orbit f (f s)"
using assms by (auto intro: orbit_step orbit_sim_step)
qed (auto intro: orbit_subset)
lemma permutation_orbit_step:
assumes "permutation f" shows "orbit f (f s) = orbit f s"
using assms by (intro self_in_orbit_step permutation_self_in_orbit)
lemma orbit_nonempty:
"orbit f s ≠ {}"
using orbit.base by fastforce
lemma orbit_inv_eq:
assumes "permutation f"
shows "orbit (inv f) x = orbit f x" (is "?L = ?R")
proof -
{ fix g y assume A: "permutation g" "y ∈ orbit (inv g) x"
have "y ∈ orbit g x"
proof -
have inv_g: "⋀y. x = g y ⟹ inv g x = y" "⋀y. inv g (g y) = y"
by (metis A(1) bij_inv_eq_iff permutation_bijective)+
{ fix y assume "y ∈ orbit g x"
then have "inv g y ∈ orbit g x"
by (cases) (simp_all add: inv_g A(1) permutation_self_in_orbit)
} note inv_g_in_orb = this
from A(2) show ?thesis
by induct (simp_all add: inv_g_in_orb A permutation_self_in_orbit)
qed
} note orb_inv_ss = this
have "inv (inv f) = f"
by (simp add: assms inv_inv_eq permutation_bijective)
then show ?thesis
using orb_inv_ss[OF assms] orb_inv_ss[OF permutation_inverse[OF assms]] by auto
qed
lemma cyclic_on_alldef:
"cyclic_on f S ⟷ S ≠ {} ∧ (∀s∈S. S = orbit f s)"
unfolding cyclic_on_def by (auto intro: orbit.step orbit_swap orbit_trans)
lemma cyclic_on_funpow_in:
assumes "cyclic_on f S" "s ∈ S" shows "(f^^n) s ∈ S"
using assms unfolding cyclic_on_def by (auto intro: funpow_in_orbit)
lemma finite_cyclic_on:
assumes "cyclic_on f S" shows "finite S"
using assms by (auto simp: cyclic_on_def finite_orbit)
lemma cyclic_on_singleI:
assumes "s ∈ S" "S = orbit f s" shows "cyclic_on f S"
using assms unfolding cyclic_on_def by blast
lemma cyclic_on_inI:
assumes "cyclic_on f S" "s ∈ S" shows "f s ∈ S"
using assms by (auto simp: cyclic_on_def intro: orbit.intros)
lemma orbit_inverse:
assumes self: "a ∈ orbit g a"
and eq: "⋀x. x ∈ orbit g a ⟹ g' (f x) = f (g x)"
shows "f ` orbit g a = orbit g' (f a)" (is "?L = ?R")
proof (intro set_eqI iffI)
fix x assume "x ∈ ?L"
then obtain x0 where "x0 ∈ orbit g a" "x = f x0" by auto
then show "x ∈ ?R"
proof (induct arbitrary: x)
case base then show ?case by (auto simp: self orbit.base eq[symmetric])
next
case step then show ?case by cases (auto simp: eq[symmetric] orbit.intros)
qed
next
fix x assume "x ∈ ?R"
then show "x ∈ ?L"
proof (induct arbitrary: )
case base then show ?case by (auto simp: self orbit.base eq)
next
case step then show ?case by cases (auto simp: eq orbit.intros)
qed
qed
lemma cyclic_on_image:
assumes "cyclic_on f S"
assumes "⋀x. x ∈ S ⟹ g (h x) = h (f x)"
shows "cyclic_on g (h ` S)"
using assms by (auto simp: cyclic_on_def) (meson orbit_inverse)
lemma cyclic_on_f_in:
assumes "f permutes S" "cyclic_on f A" "f x ∈ A"
shows "x ∈ A"
proof -
from assms have fx_in_orb: "f x ∈ orbit f (f x)" by (auto simp: cyclic_on_alldef)
from assms have "A = orbit f (f x)" by (auto simp: cyclic_on_alldef)
moreover
then have "… = orbit f x" using ‹f x ∈ A› by (auto intro: orbit_step orbit_subset)
ultimately
show ?thesis by (metis (no_types) orbit.simps permutes_inverses(2)[OF assms(1)])
qed
lemma orbit_cong0:
assumes "x ∈ A" "f ∈ A → A" "⋀y. y ∈ A ⟹ f y = g y" shows "orbit f x = orbit g x"
proof -
{ fix n have "(f ^^ n) x = (g ^^ n) x ∧ (f ^^ n) x ∈ A"
by (induct n rule: nat.induct) (insert assms, auto)
} then show ?thesis by (auto simp: orbit_altdef)
qed
lemma orbit_cong:
assumes self_in: "t ∈ orbit f t" and eq: "⋀s. s ∈ orbit f t ⟹ g s = f s"
shows "orbit g t = orbit f t"
using assms(1) _ assms(2) by (rule orbit_cong0) (auto simp: orbit.step eq)
lemma cyclic_cong:
assumes "⋀s. s ∈ S ⟹ f s = g s" shows "cyclic_on f S = cyclic_on g S"
proof -
have "(∃s∈S. orbit f s = orbit g s) ⟹ cyclic_on f S = cyclic_on g S"
by (metis cyclic_on_alldef cyclic_on_def)
then show ?thesis by (metis assms orbit_cong cyclic_on_def)
qed
lemma permutes_comp_preserves_cyclic1:
assumes "g permutes B" "cyclic_on f C"
assumes "A ∩ B = {}" "C ⊆ A"
shows "cyclic_on (f o g) C"
proof -
have *: "⋀c. c ∈ C ⟹ f (g c) = f c"
using assms by (subst permutes_not_in [of g]) auto
with assms(2) show ?thesis by (simp cong: cyclic_cong)
qed
lemma permutes_comp_preserves_cyclic2:
assumes "f permutes A" "cyclic_on g C"
assumes "A ∩ B = {}" "C ⊆ B"
shows "cyclic_on (f o g) C"
proof -
obtain c where c: "c ∈ C" "C = orbit g c" "c ∈ orbit g c"
using ‹cyclic_on g C› by (auto simp: cyclic_on_def)
then have "⋀c. c ∈ C ⟹ f (g c) = g c"
using assms c by (subst permutes_not_in [of f]) (auto intro: orbit.intros)
with assms(2) show ?thesis by (simp cong: cyclic_cong)
qed
lemma permutes_orbit_subset:
assumes "f permutes S" "x ∈ S" shows "orbit f x ⊆ S"
proof
fix y assume "y ∈ orbit f x"
then show "y ∈ S" by induct (auto simp: permutes_in_image assms)
qed
lemma cyclic_on_orbit':
assumes "permutation f" shows "cyclic_on f (orbit f x)"
unfolding cyclic_on_alldef using orbit_nonempty[of f x]
by (auto intro: assms orbit_swap orbit_trans permutation_self_in_orbit)
lemma cyclic_on_orbit:
assumes "f permutes S" "finite S" shows "cyclic_on f (orbit f x)"
using assms by (intro cyclic_on_orbit') (auto simp: permutation_permutes)
lemma orbit_cyclic_eq3:
assumes "cyclic_on f S" "y ∈ S" shows "orbit f y = S"
using assms unfolding cyclic_on_alldef by simp
lemma orbit_eq_singleton_iff: "orbit f x = {x} ⟷ f x = x" (is "?L ⟷ ?R")
proof
assume A: ?R
{ fix y assume "y ∈ orbit f x" then have "y = x"
by induct (auto simp: A)
} then show ?L by (metis orbit_nonempty singletonI subsetI subset_singletonD)
next
assume A: ?L
then have "⋀y. y ∈ orbit f x ⟹ f x = y"
by - (erule orbit.cases, simp_all)
then show ?R using A by blast
qed
lemma eq_on_cyclic_on_iff1:
assumes "cyclic_on f S" "x ∈ S"
obtains "f x ∈ S" "f x = x ⟷ card S = 1"
proof
from assms show "f x ∈ S" by (auto simp: cyclic_on_def intro: orbit.intros)
from assms have "S = orbit f x" by (auto simp: cyclic_on_alldef)
then have "f x = x ⟷ S = {x}" by (metis orbit_eq_singleton_iff)
then show "f x = x ⟷ card S = 1" using ‹x ∈ S› by (auto simp: card_Suc_eq)
qed
lemma orbit_eqI:
"y = f x ⟹ y ∈ orbit f x"
"z = f y ⟹y ∈ orbit f x ⟹z ∈ orbit f x"
by (metis orbit.base) (metis orbit.step)
subsection ‹Decomposition of arbitrary permutations›
definition perm_restrict :: "('a ⇒ 'a) ⇒ 'a set ⇒ ('a ⇒ 'a)" where
"perm_restrict f S x ≡ if x ∈ S then f x else x"
lemma perm_restrict_comp:
assumes "A ∩ B = {}" "cyclic_on f B"
shows "perm_restrict f A o perm_restrict f B = perm_restrict f (A ∪ B)"
proof -
have "⋀x. x ∈ B ⟹ f x ∈ B" using ‹cyclic_on f B› by (rule cyclic_on_inI)
with assms show ?thesis by (auto simp: perm_restrict_def fun_eq_iff)
qed
lemma perm_restrict_simps:
"x ∈ S ⟹ perm_restrict f S x = f x"
"x ∉ S ⟹ perm_restrict f S x = x"
by (auto simp: perm_restrict_def)
lemma perm_restrict_perm_restrict:
"perm_restrict (perm_restrict f A) B = perm_restrict f (A ∩ B)"
by (auto simp: perm_restrict_def)
lemma perm_restrict_union:
assumes "perm_restrict f A permutes A" "perm_restrict f B permutes B" "A ∩ B = {}"
shows "perm_restrict f A o perm_restrict f B = perm_restrict f (A ∪ B)"
using assms by (auto simp: fun_eq_iff perm_restrict_def permutes_def) (metis Diff_iff Diff_triv)
lemma perm_restrict_id[simp]:
assumes "f permutes S" shows "perm_restrict f S = f"
using assms by (auto simp: permutes_def perm_restrict_def)
lemma cyclic_on_perm_restrict:
"cyclic_on (perm_restrict f S) S ⟷ cyclic_on f S"
by (simp add: perm_restrict_def cong: cyclic_cong)
lemma perm_restrict_diff_cyclic:
assumes "f permutes S" "cyclic_on f A"
shows "perm_restrict f (S - A) permutes (S - A)"
proof -
{ fix y
have "∃x. perm_restrict f (S - A) x = y"
proof cases
assume A: "y ∈ S - A"
with ‹f permutes S› obtain x where "f x = y" "x ∈ S"
unfolding permutes_def by auto metis
moreover
with A have "x ∉ A" by (metis Diff_iff assms(2) cyclic_on_inI)
ultimately
have "perm_restrict f (S - A) x = y" by (simp add: perm_restrict_simps)
then show ?thesis ..
next
assume "y ∉ S - A"
then have "perm_restrict f (S - A) y = y" by (simp add: perm_restrict_simps)
then show ?thesis ..
qed
} note X = this
{ fix x y assume "perm_restrict f (S - A) x = perm_restrict f (S - A) y"
with assms have "x = y"
by (auto simp: perm_restrict_def permutes_def split: if_splits intro: cyclic_on_f_in)
} note Y = this
show ?thesis by (auto simp: permutes_def perm_restrict_simps X intro: Y)
qed
lemma permutes_decompose:
assumes "f permutes S" "finite S"
shows "∃C. (∀c ∈ C. cyclic_on f c) ∧ ⋃C = S ∧ (∀c1 ∈ C. ∀c2 ∈ C. c1 ≠ c2 ⟶ c1 ∩ c2 = {})"
using assms(2,1)
proof (induction arbitrary: f rule: finite_psubset_induct)
case (psubset S)
show ?case
proof (cases "S = {}")
case True then show ?thesis by (intro exI[where x="{}"]) auto
next
case False
then obtain s where "s ∈ S" by auto
with ‹f permutes S› have "orbit f s ⊆ S"
by (rule permutes_orbit_subset)
have cyclic_orbit: "cyclic_on f (orbit f s)"
using ‹f permutes S› ‹finite S› by (rule cyclic_on_orbit)
let ?f' = "perm_restrict f (S - orbit f s)"
have "f s ∈ S" using ‹f permutes S› ‹s ∈ S› by (auto simp: permutes_in_image)
then have "S - orbit f s ⊂ S" using orbit.base[of f s] ‹s ∈ S› by blast
moreover
have "?f' permutes (S - orbit f s)"
using ‹f permutes S› cyclic_orbit by (rule perm_restrict_diff_cyclic)
ultimately
obtain C where C: "⋀c. c ∈ C ⟹ cyclic_on ?f' c" "⋃C = S - orbit f s"
"∀c1 ∈ C. ∀c2 ∈ C. c1 ≠ c2 ⟶ c1 ∩ c2 = {}"
using psubset.IH by metis
{ fix c assume "c ∈ C"
then have *: "⋀x. x ∈ c ⟹ perm_restrict f (S - orbit f s) x = f x"
using C(2) ‹f permutes S› by (auto simp add: perm_restrict_def)
then have "cyclic_on f c" using C(1)[OF ‹c ∈ C›] by (simp cong: cyclic_cong add: *)
} note in_C_cyclic = this
have Un_ins: "⋃(insert (orbit f s) C) = S"
using ‹⋃C = _› ‹orbit f s ⊆ S› by blast
have Disj_ins: "(∀c1 ∈ insert (orbit f s) C. ∀c2 ∈ insert (orbit f s) C. c1 ≠ c2 ⟶ c1 ∩ c2 = {})"
using C by auto
show ?thesis
by (intro conjI Un_ins Disj_ins exI[where x="insert (orbit f s) C"])
(auto simp: cyclic_orbit in_C_cyclic)
qed
qed
subsection ‹Function-power distance between values›
definition funpow_dist :: "('a ⇒ 'a) ⇒ 'a ⇒ 'a ⇒ nat" where
"funpow_dist f x y ≡ LEAST n. (f ^^ n) x = y"
abbreviation funpow_dist1 :: "('a ⇒ 'a) ⇒ 'a ⇒ 'a ⇒ nat" where
"funpow_dist1 f x y ≡ Suc (funpow_dist f (f x) y)"
lemma funpow_dist_0:
assumes "x = y" shows "funpow_dist f x y = 0"
using assms unfolding funpow_dist_def by (intro Least_eq_0) simp
lemma funpow_dist_least:
assumes "n < funpow_dist f x y" shows "(f ^^ n) x ≠ y"
proof (rule notI)
assume "(f ^^ n) x = y"
then have "funpow_dist f x y ≤ n" unfolding funpow_dist_def by (rule Least_le)
with assms show False by linarith
qed
lemma funpow_dist1_least:
assumes "0 < n" "n < funpow_dist1 f x y" shows "(f ^^ n) x ≠ y"
proof (rule notI)
assume "(f ^^ n) x = y"
then have "(f ^^ (n - 1)) (f x) = y"
using ‹0 < n› by (cases n) (simp_all add: funpow_swap1)
then have "funpow_dist f (f x) y ≤ n - 1" unfolding funpow_dist_def by (rule Least_le)
with assms show False by simp
qed
lemma funpow_dist_prop:
"y ∈ orbit f x ⟹ (f ^^ funpow_dist f x y) x = y"
unfolding funpow_dist_def by (rule LeastI_ex) (auto simp: orbit_altdef)
lemma funpow_dist_0_eq:
assumes "y ∈ orbit f x" shows "funpow_dist f x y = 0 ⟷ x = y"
using assms by (auto simp: funpow_dist_0 dest: funpow_dist_prop)
lemma funpow_dist_step:
assumes "x ≠ y" "y ∈ orbit f x" shows "funpow_dist f x y = Suc (funpow_dist f (f x) y)"
proof -
from ‹y ∈ _› obtain n where "(f ^^ n) x = y" by (auto simp: orbit_altdef)
with ‹x ≠ y› obtain n' where [simp]: "n = Suc n'" by (cases n) auto
show ?thesis
unfolding funpow_dist_def
proof (rule Least_Suc2)
show "(f ^^ n) x = y" by fact
then show "(f ^^ n') (f x) = y" by (simp add: funpow_swap1)
show "(f ^^ 0) x ≠ y" using ‹x ≠ y› by simp
show "∀k. ((f ^^ Suc k) x = y) = ((f ^^ k) (f x) = y)"
by (simp add: funpow_swap1)
qed
qed
lemma funpow_dist1_prop:
assumes "y ∈ orbit f x" shows "(f ^^ funpow_dist1 f x y) x = y"
by (metis assms funpow_dist_prop funpow_dist_step funpow_simps_right(2) o_apply self_in_orbit_step)
lemma funpow_neq_less_funpow_dist:
assumes "y ∈ orbit f x" "m ≤ funpow_dist f x y" "n ≤ funpow_dist f x y" "m ≠ n"
shows "(f ^^ m) x ≠ (f ^^ n) x"
proof (rule notI)
assume A: "(f ^^ m) x = (f ^^ n) x"
define m' n' where "m' = min m n" and "n' = max m n"
with A assms have A': "m' < n'" "(f ^^ m') x = (f ^^ n') x" "n' ≤ funpow_dist f x y"
by (auto simp: min_def max_def)
have "y = (f ^^ funpow_dist f x y) x"
using ‹y ∈ _› by (simp only: funpow_dist_prop)
also have "… = (f ^^ ((funpow_dist f x y - n') + n')) x"
using ‹n' ≤ _› by simp
also have "… = (f ^^ ((funpow_dist f x y - n') + m')) x"
by (simp add: funpow_add ‹(f ^^ m') x = _›)
also have "(f ^^ ((funpow_dist f x y - n') + m')) x ≠ y"
using A' by (intro funpow_dist_least) linarith
finally show "False" by simp
qed
lemma funpow_neq_less_funpow_dist1:
assumes "y ∈ orbit f x" "m < funpow_dist1 f x y" "n < funpow_dist1 f x y" "m ≠ n"
shows "(f ^^ m) x ≠ (f ^^ n) x"
proof (rule notI)
assume A: "(f ^^ m) x = (f ^^ n) x"
define m' n' where "m' = min m n" and "n' = max m n"
with A assms have A': "m' < n'" "(f ^^ m') x = (f ^^ n') x" "n' < funpow_dist1 f x y"
by (auto simp: min_def max_def)
have "y = (f ^^ funpow_dist1 f x y) x"
using ‹y ∈ _› by (simp only: funpow_dist1_prop)
also have "… = (f ^^ ((funpow_dist1 f x y - n') + n')) x"
using ‹n' < _› by simp
also have "… = (f ^^ ((funpow_dist1 f x y - n') + m')) x"
by (simp add: funpow_add ‹(f ^^ m') x = _›)
also have "(f ^^ ((funpow_dist1 f x y - n') + m')) x ≠ y"
using A' by (intro funpow_dist1_least) linarith+
finally show "False" by simp
qed
lemma inj_on_funpow_dist:
assumes "y ∈ orbit f x" shows "inj_on (λn. (f ^^ n) x) {0..funpow_dist f x y}"
using funpow_neq_less_funpow_dist[OF assms] by (intro inj_onI) auto
lemma inj_on_funpow_dist1:
assumes "y ∈ orbit f x" shows "inj_on (λn. (f ^^ n) x) {0..<funpow_dist1 f x y}"
using funpow_neq_less_funpow_dist1[OF assms] by (intro inj_onI) auto
lemma orbit_conv_funpow_dist1:
assumes "x ∈ orbit f x"
shows "orbit f x = (λn. (f ^^ n) x) ` {0..<funpow_dist1 f x x}" (is "?L = ?R")
using funpow_dist1_prop[OF assms]
by (auto simp: orbit_altdef_bounded[where n="funpow_dist1 f x x"])
lemma funpow_dist1_prop1:
assumes "(f ^^ n) x = y" "0 < n" shows "(f ^^ funpow_dist1 f x y) x = y"
proof -
from assms have "y ∈ orbit f x" by (auto simp: orbit_altdef)
then show ?thesis by (rule funpow_dist1_prop)
qed
lemma funpow_dist1_dist:
assumes "funpow_dist1 f x y < funpow_dist1 f x z"
assumes "{y,z} ⊆ orbit f x"
shows "funpow_dist1 f x z = funpow_dist1 f x y + funpow_dist1 f y z" (is "?L = ?R")
proof -
define n where ‹n = funpow_dist1 f x z - funpow_dist1 f x y - 1›
with assms have *: ‹funpow_dist1 f x z = Suc (funpow_dist1 f x y + n)›
by simp
have x_z: "(f ^^ funpow_dist1 f x z) x = z" using assms by (blast intro: funpow_dist1_prop)
have x_y: "(f ^^ funpow_dist1 f x y) x = y" using assms by (blast intro: funpow_dist1_prop)
have "(f ^^ (funpow_dist1 f x z - funpow_dist1 f x y)) y
= (f ^^ (funpow_dist1 f x z - funpow_dist1 f x y)) ((f ^^ funpow_dist1 f x y) x)"
using x_y by simp
also have "… = z"
using assms x_z by (simp add: * funpow_add ac_simps funpow_swap1)
finally have y_z_diff: "(f ^^ (funpow_dist1 f x z - funpow_dist1 f x y)) y = z" .
then have "(f ^^ funpow_dist1 f y z) y = z"
using assms by (intro funpow_dist1_prop1) auto
then have "(f ^^ funpow_dist1 f y z) ((f ^^ funpow_dist1 f x y) x) = z"
using x_y by simp
then have "(f ^^ (funpow_dist1 f y z + funpow_dist1 f x y)) x = z"
by (simp add: * funpow_add funpow_swap1)
show ?thesis
proof (rule antisym)
from y_z_diff have "(f ^^ funpow_dist1 f y z) y = z"
using assms by (intro funpow_dist1_prop1) auto
then have "(f ^^ funpow_dist1 f y z) ((f ^^ funpow_dist1 f x y) x) = z"
using x_y by simp
then have "(f ^^ (funpow_dist1 f y z + funpow_dist1 f x y)) x = z"
by (simp add: * funpow_add funpow_swap1)
then have "funpow_dist1 f x z ≤ funpow_dist1 f y z + funpow_dist1 f x y"
using funpow_dist1_least not_less by fastforce
then show "?L ≤ ?R" by presburger
next
have "funpow_dist1 f y z ≤ funpow_dist1 f x z - funpow_dist1 f x y"
using y_z_diff assms(1) by (metis not_less zero_less_diff funpow_dist1_least)
then show "?R ≤ ?L" by linarith
qed
qed
lemma funpow_dist1_le_self:
assumes "(f ^^ m) x = x" "0 < m" "y ∈ orbit f x"
shows "funpow_dist1 f x y ≤ m"
proof (cases "x = y")
case True with assms show ?thesis by (auto dest!: funpow_dist1_least)
next
case False
have "(f ^^ funpow_dist1 f x y) x = (f ^^ (funpow_dist1 f x y mod m)) x"
using assms by (simp add: funpow_mod_eq)
with False ‹y ∈ orbit f x› have "funpow_dist1 f x y ≤ funpow_dist1 f x y mod m"
by auto (metis ‹(f ^^ funpow_dist1 f x y) x = (f ^^ (funpow_dist1 f x y mod m)) x› funpow_dist1_prop funpow_dist_least funpow_dist_step leI)
with ‹m > 0› show ?thesis
by (auto intro: order_trans)
qed
end